2020
DOI: 10.18203/2394-6040.ijcmph20205683
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of dengue hemorrhagic fever in Talaud Islands regency

Abstract: Background: The number of dengue hemorrhagic fever (DHF) cases in Indonesia from January to February 2016 was 8,487 with 108 deaths. DHF is an infectious disease that continues to increase from 2014 until 2016 in Manado city. DHF cases in Talaud Islands Regency from 2014 to 2016 were 143 cases. Regional spatial analysis would simplify the distribution of DHF cases in high-risk areas. To be aware of the DHF outbreak cycle, it is necessary to model spatial risk factors based on geographic information systems (GI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…Spatial analysis using regional risk factor modeling will facilitate the control and management of dengue cases, especially in the distribution of dengue cases in high-risk areas. Spatial analysis based on Geographic Information Systems (GIS) can be used to be aware of potential outbreaks per region (Mandagi, Kalesaran and Kolibu, 2021). A study in Nepal by Acharya et al using the SATsan application showed that the spread of DHF was not random but clustered in space and time in the Chitwan and Jhapa areas (Acharya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial analysis using regional risk factor modeling will facilitate the control and management of dengue cases, especially in the distribution of dengue cases in high-risk areas. Spatial analysis based on Geographic Information Systems (GIS) can be used to be aware of potential outbreaks per region (Mandagi, Kalesaran and Kolibu, 2021). A study in Nepal by Acharya et al using the SATsan application showed that the spread of DHF was not random but clustered in space and time in the Chitwan and Jhapa areas (Acharya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%